(untitled) (Singaporean Journal of Business Economics and Management, 2019)
Using IT capabilities is one the effective factors in attracting tourists which led to a new concept formation called E-Tourism and caused a tremendous transformation in this industry. Therefore, the E-marketing tools and its capability in attracting tourist to Tehran were evaluated and prioritized in this study. Experts and elites related to E-marketing as well as Tehran residents are the statistical population of this research. To achieve the desired goals, one-sample t-test and binomial t-test were used. Data analysis has been performed by using SPSS software. Based on the results, online advertising, social network marketing, website optimization, search engines, blogging, and SMS advertising have a significant impact on attracting tourists, but online advertising, social network marketing and website optimization have the most substantial impact on attracting tourists. However, website optimization with mean rank of 5.36, online advertising with mean rank of 5.08, search engines with mean rank of 3.90 and Texts Ads (SMS) with mean rank of 3.87 are the most influential factors in attracting tourists, respectively.